2016
DOI: 10.1097/coc.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Positive Margins on Outcome Among Patients With Gastric Cancer Treated With Radiation

Abstract: Positive margins were associated with recurrence despite aggressive multimodality therapy including radiotherapy and the selective use of chemotherapy. Thus, additional consideration is warranted for strategies such as neoadjuvant chemoradiation intended to facilitate complete resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Multiple prospective randomized trials regarding the influence of the R1 margin on gastric cancer survival have been conducted in Asian and Western populations, but the results have been controversial [66][67][68]. Several authors found that positive margins are an independent risk factor for survival following gastric resection for cancer [69].…”
Section: Influence Of Positive Resection Margins and Re-resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple prospective randomized trials regarding the influence of the R1 margin on gastric cancer survival have been conducted in Asian and Western populations, but the results have been controversial [66][67][68]. Several authors found that positive margins are an independent risk factor for survival following gastric resection for cancer [69].…”
Section: Influence Of Positive Resection Margins and Re-resectionmentioning
confidence: 99%
“…A multivariate regression analysis performed by Bickenbach [70] showed that R1 margins were associated with poor survival, but this association was only observed in patients with fewer than three positive lymph nodes or T1-2 disease. Schoenfeld et al [68] showed that R1 margins were associated with a lower disease-free interval, but overall survival rates were comparable to those for R0. Regarding the opportunity for a re-resection following R1, Raziee et al [69] obtained controversial results via a systematic review, but they agreed that re-resection should be performed to eliminate the R1 margin whenever feasible [71].…”
Section: Influence Of Positive Resection Margins and Re-resectionmentioning
confidence: 99%
“…Twelve studies 3 , 12 , 15 , 16 , 17 , 22 , 43 45 , 47 49 reported HRs, and the necessary statistics were extracted from the Kaplan–Meier curves in two studies. 8 , 9 Adding these, 14 studies were selected to estimate pooled HR.…”
Section: Overall Survivalmentioning
confidence: 99%
“… 5 , 6 Although the impact of microscopically positive (R1) margins (cancer cells present at the resection margin on pathological examination) on survival in GC has been discussed in many studies, inconsistent conclusions have been reported. 2 , 5 , 7 - 16 Kim et al 15 and Postlewait et al 12 found that R1 margin was not independently associated with survival, while Woo et al 12 and Nagata et al 5 revealed that it boded ill for survival. Bickenbach et al 10 reported that R1 margin was an independent predictor of worse survival but not in patients with more than three positive nodes or T3–4 disease.…”
Section: Introductionmentioning
confidence: 99%
“…Bickenbach et al 11 found that R1 margin was an independent predictor of worse survival, but not in patients with >3 positive nodes or T3–4 disease. Schoenfeld et al 18 found R1 margins were associated with disease-free survival (DFS) but not overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%